Individual and Community-Level Risk Factors for Giardiasis in Children under Five Years of Age in Pakistan: A Prospective Multi-Regional Study - Irfan Khattak; Wen-Lan Yen; Tahir Usman; Nasreen Nasreen; Adil Khan; Saghir Ahmad; Gauhar Rehman; Khurshaid Khan; Mourad Ben Said; Chien-Chin Chen (MDPI AG, 2023)
Objectives: This study aimed to estimate the prevalence of Giardia lamblia infection and identify associated risk factors at both individual and community levels in a pediatric population in different agroecological zones of Khyber Pakhtunkhwa, Pakistan. Methods: A community-based cross-sectional study was conducted from March to December 2022. Using stratified sampling, 1026 households were recruited from nine agroecological zones. Stool samples were collected from 1026 children up to the age of five years and processed for detection of Giardia using a commercial ELISA kit. Data on potential risk factors were collected using a pre-structured questionnaire. A multivariable logistic regression model was used to identify risk factors associated with giardiasis. Results: The study found that the prevalence of giardiasis in the study area was 3.31%. Children aged 13-24 months were found to be at higher risk for giardiasis. Illiterate mothers and fathers attending daycare institutions/kindergartens, mothers not practicing hand washing during critical times, households with companion animals, and homes where stray dogs/cats enter were identified as predictors of giardiasis at the individual level. Children living in sub-mountain valleys use un-piped water, inadequate domestic water storage vessels, drink un-boiled or unfiltered water, live near rubbish heaps or un-paved streets/pathways, and have unimproved latrine facilities were identified as risk factors of giardiasis at the community level. Conclusions: The study highlights the need for integrated intervention approaches at both individual and community levels to reduce the incidence of giardiasis in Khyber Pakhtunkhwa, Pakistan. Interventions aimed at promoting behavioral change and providing safe and adequate water sources, combined with individual-level interventions such as hand washing and awareness of giardiasis prevention methods, would be critical to addressing this health concern. Inter-sectoral collaboration between the health sector and other sectors would also be necessary to achieve meaningful progress in reducing the incidence of giardiasis in resource-limited areas.